Exercise-Based Injury Prevention in High-Level and Professional Athletes: Narrative Review and Proposed Standard Operating Procedure for Future Lockdown-Like Contexts After COVID-19 - Martens, Géraldine; Delvaux, François; Forthomme, Bénédicte; Kaux, Jean-François; Urhausen, Axel; Bieuzen, François; Leclerc, Suzanne; Winkler, Laurent; Brocherie, Franck; Nedelec, Mathieu; Morales-Artacho, Antonio J.; Ruffault, Alexis; et al. (Frontiers in Sports and Active Living, 2021)
In regular times, implementing exercise-based injury prevention programs into the training routine of high-level and professional athletes represents a key and challenging aspect to decrease injury risk. Barriers to implementing such prevention programs have previously been identified such as lack of resources, logistic issues or motivation. The COVID-19 pandemic associated with restrictions on daily life dramatically impacted sports participation from training to competition. It is therefore reasonable to assume that such lockdown-like context has exacerbated the challenge to implement exercise-based injury prevention programs, potentially leading to a greater musculoskeletal injury risk. In this narrative review, recommendations are proposed for building an expertise- and evidence-based Standard Operating Procedure for injury prevention in lockdown-like contexts for high-level and professional athletes. The following recommendations can be provided: (1) assess the global and sport-specific risks in the light of the ongoing cause of isolation; (2) adapt remote training materials and programs; (3) ensure regular quality communication within the staff, between athletes and the staff as well as between athletes; (4) follow the athlete's mental well-being; and (5) plan for a safe return-to-sports as well as for an ongoing monitoring of the load-recovery balance. These key domains should further be addressed to comply with local policies, which are subject to change over time in each individual country. The use of these recommendations may improve the readiness of athletes, coaches, physicians and all sports stakeholders for future lockdown-like contexts.